A Theology of Leadership, not Management: Trinitarian Mission and Baptismal Discipleship - Bevans, Stephen (Annales Missiologici Posnanienses, 2017)
The understanding of leadership and or experience of leaders have permanently changed, and the key questions for today’s no longer issues of task and structure but are questions of spirit. The models of leadership are connecting with mission hence the roots ministry are not in the acquisition of skills, but in a changed attitude toward others, a conversion, and a new way of looking at the world. In this perspective is presented a theology of leadership: tree theological paradigm shifts, Trinitarian Mission and baptismal discipleship.